Secure ICT service provisioning for cloud, mobile and beyond a workable architectural approach balancing between buyers and providers - Von Faber, Eberhard (Springer Vieweg, 2013)
Introduces a reference architecture that enhances the security of services offered in the information and communication technology (ICT) market. This title enables customers to compare offerings and to assess risks when using third-party ICT services including cloud computing and mobile services.